Ovarian cancer in situ: a case report - A. N. Turomsha; A. E. Protasova; G. A. Raskin; E. D. Kravtsova; A. L. Andreev; L. V. Strakh; M. Yu. Sheremet (Опухоли женской репродуктивной системы, 2024)
In most cases, ovarian cancer is diagnosed at advanced stages, leading to a poor prognosis. Currently, there is no effective screening for ovarian cancer, so detecting it in the early stages is a fairly successful case.